A Computational Alanine Scanning of Heptapeptide RRRSAGM Targeting Dengue NS2B/NS3 Protease - Ismail, Ahmad Ghazali; Abdalrazaq, Nadeem Abdalsatar; Mohd Rawi, Mohd Faizul Ridzal; Mohamad, Suriani; Wahab, Habibah A.; Kamarulzaman, Ezatul Ezleen (Trends in Sciences, 2022)
The pathogenic dengue virus (DV) transmitted mainly by the Aedes aegypti mosquito has been the most rapidly spreading mosquito-borne viral disease and became a serious threat to global health issue in tropical and sub-tropical countries. The clinical symptoms ranging from mild to a fatal dengue hemorrhagic fever and dengue shock syndrome, characterized by failure of the circulation system that may lead to death. There are still no drugs or vaccines available in the market to prevent or treat dengue infections. Hence, the development of successful drugs that are safe and offer a long-lasting protection against dengue viruses is needed. Recently, the discovery of peptides with high specificity, selectivity, and efficacy; and relatively safer than small-molecule drugs have become a promising agent for a new drug. Previously, a molecular dynamic simulation reported that peptide NRRRRSAGMI from the capsid’s cleavage region had the most hydrogen bonds with NS2B/NS3 protease, thus it leads into a starting linear heptapeptide R(P3)-R(P2)-R(P1)-S(P1’)-A(P2’)-G(P3’)-M(P4’). This study aimed to investigate the importance and specificity of individual amino acid residue of the heptapeptide substrate on the binding affinity and interaction to NS2B/NS3 dengue protease through computational alanine scanning. It showed that the changing of P1 and P2 arginine to alanine resulted to higher values of binding affinity. Thus, the arginine is an important residue at the P1 and P2 positions for the binding of the substrate peptide to DENV NS2B/NS3 protease, hence the amino acid residues which are essential for the enzyme-substrate interactions can be predicted through computational alanine scanning. HIGHLIGHTS Dengue is a mosquito-transmitted virus cause of arthropod-borne viral disease The discovery of peptides became a potential agent for dengue virus and previously peptide NRRRRSAGMI has been reported as starting linear heptapeptide RRRSAGM A computational alanine scanning based on the peptide RRRSAGM has been performed S1 and S2 pockets show strong preferences for basic amino acids, whereas the S3 pocket is less selective for basic residue The arginine at P1 and P2 positions of the heptapeptide substrate contribute significantly to the substrate binding affinity GRAPHICAL ABSTRACT